Study of the Effect of Simulated Rain on the Offset Parabolic Antenna at Ku-Band with Different Elevation Angles. (3rd June 2007) - Mostafa, H.; Hassan, S. I. S.; Mandeep, J. S.; Ain, M. F.; Khedher, H. A.
Abstract : Effect of rain on the receiver antenna is a major factor to degrade the system performance in a frequency above 10 GHz. This paper deals with the wet antenna attenuation at Ku-band with three different frequencies at different rain rates. During the Ku-band propagation experiment, it was discovered that rain water on the antenna caused a significant attenuation. It is necessary to estimate the losses caused by water on the antenna in order to separate these losses from the atmospheric propagation losses. The experiment was done at USM Engineering Campus to study the attenuation for these physical parameters. A Ku-band RF signal was generated by a signal generator and transmitted via horn antenna. The signal was received using a smooth offset antenna of 60 cm by 54 cm (Astro dish) and measured using spectrum analyzer. In order to simulate a rain, pipes with bores of a same distance were implemented. Three cases were considered: in the first case one pipe was used to simulate low rain rate, the second case two pipes were used to simulate medium rain rate, and the third case three pipes were used to simulate heavy rain rate. In addition, the tap was used to control the flow of water in order to get more values of rain rate. The total attenuation of RF signals due to water layer on the feed and on the reflector feed was found to be 3.1 dB at worst case. On the other hand, the attenuation of RF signal due to the feed only was 2.83 dB, so the major attenuation occur was due to feed.